Management of Low Back Pain by Physical Therapists in Quebec: How Are We Doing? - Derghazarian, Tamar (University of Toronto Press Incorporated, 2011)
Purpose: In this study, we characterized physiotherapists' attitudes and beliefs about the bio-psychosocial problem of low back pain (LBP), their use of clinical practice guidelines (CPGs), and the extent to which their advice and treatment is in line with best-evidence CPGs. Methods: One hundred eight physiotherapists completed an online survey that included questionnaires exploring the strength of physiotherapists' biomedical and bio-psychosocial orientations toward the management of LBP: the Pain Attitudes and Beliefs Scale for Physiotherapists and the Attitudes to Back Pain Scale for musculoskeletal practitioners. In addition, participants responded to questions about treatment recommendations for patients in two vignettes. Results: Only 12% of respondents were aware of CPGs. Physiotherapists with a stronger biomedical orientation scored the severity of spinal pathology higher in the patient vignettes. A stronger biomedical orientation was also associated with disagreement with recommendations to return to usual activity or work. Conclusions: The results suggest limited awareness by physiotherapists of best-evidence CPGs and contemporary understandings of LBP that support early activation and self-management. Research to better understand and facilitate the implementation of best-evidence professional education and clinical practice is an urgent priority.